Criminal Liability for Indonesians Who Use Digital Wallets to Commit Child Sexual Exploitation - Karima Naila Putri; Kiki Kristanto; Yurika F.Dewi (Dinasti Research, 2025)
The ease of access to digital financial services, such as digital wallets, has strengthened the effectiveness of cyber influence techniques as a tool for criminals. Digital wallets offer convenience in financial transactions without requiring physical presence or strict identification, increasing the risk of misuse. In the context of child sexual exploitation, social engineering techniques leveraging digital wallets can have devastating impacts. Perpetrators may deceive child victims, their families, or financial service providers to gain financial resources for committing crimes. This research addresses two key questions: how perpetrators use influence techniques and digital wallets to commit child sexual exploitation, and how Indonesian law addresses their criminal liability. The study employs prescriptive legal research to analyze coherence between legal norms and behavior, utilizing a conceptual and statutory approach to identify the legal basis for criminal liability. Perpetrators often manipulate victims gradually, employing persuasion, pretexting, phishing, or threats. The accessibility of digital wallets enables these actions, facilitating payments while evading stricter identification processes. Although perpetrators are held liable under laws such as the Child Protection Law, the Pornography Law, and the Criminal Code, enforcement challenges persist. Strengthening legal frameworks, enhancing law enforcement, and raising public awareness are essential measures to safeguard children from such crimes.